RE-HAK: A Novel Refurbish-to-Host Solution Using AI-Driven Blockchain to Advance Circular Economy and Revitalize Japan’s Akiyas - Manuel Herrador; Wil de Jong; Kiyokazu Nasu; Lorenz Granrath (Buildings)
In recent decades, Japan has faced rural depopulation due to urban migration, resulting in widespread property abandonment, the “Akiyas”. This paper presents RE-HAK (Refurbish to Host in Akiyas), a blockchain-based framework promoting a circular economy (CE). RE-HAK enables occupants to live rent-free in Akiyas by completing AI-managed refurbishment milestones via smart contracts. Each milestone—waste removal, structural repairs, or energy upgrades—is verified and recorded on the blockchain. Benefits include: (1) rural economic revival through restoration incentives; (2) sustainable CE adoption; (3) preserving property values by halting deterioration; (4) safeguarding cultural heritage via traditional architecture restoration; and (5) transparent management through automated contracts, minimizing disputes. Findings from three case studies demonstrate RE-HAK’s adaptability across skill levels and project scales, though limitations such as rural digital literacy gaps and reliance on government support for scalability are noted. The framework advances Japan’s revitalization goals while offering a replicable model for nations facing depopulation and property abandonment, contingent on addressing technological and policy barriers.